ETHNOPOLITICAL CONFLICTS IN THE NORTHERN CAUCASUS TODAY - KHUNAGOV, Rashid; LYAUSHEVA, Svetlana; SHADZHE, Asiet; ZHADE, Zuriet (CENTRAL ASIA AND THE CAUCASUS, 2017)
Political science, history, economics, linguistics, sociology, literary studies, social psychology, and social philosophy all offer unique perspectives on the communication between people. Today, it is essential to develop common frameworks for understanding ethnopolitical conflicts as theoretical and cognitive tasks, particularly in the context of Caucasian realities. This region is increasingly becoming a crucial component of global political and social organization and is gaining importance in horizontal structuring of society. Regional conflicts and their resolution methods have become a constant focus for international organizations, including the OSCE, the U.N., its General Assembly, and the Security Council, as well as the activities of the U.N. Secretary-General. Recently, the Northern Caucasus has emerged as a hotspot for intense ethnic conflicts, negatively impacting its social and political environment. The sovereignty of the republics in Southern Russia has fragmented the region's social and political space, heightening both latent and overt national and ethnic tensions and leading to armed clashes. The ongoing events have exacerbated the North Caucasian social and political situation and brought local and tourist security concerns to the forefront. Additionally, the region is involved in the Abkhazian and South Ossetian issues and the system of trans-regional ethnic and political relationships. There is a real risk that the region could descend into international terrorism and extremism amid tensions caused by migration and social upheavals.